Determination of Natural Radioactivity and Radiological Hazards of 226Ra, 232Th, and 40K in the Grains Available at Penang Markets, Malaysia, Using High-purity Germanium Detector - Salih, Najeba F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
In the present study, the concentrations of 226Ra, 232Th, and 40K and their radiological hazards in 18 types of grain samples, collected from local markets in Penang, Malaysia, are investigated using high-purity germanium detector (HPGe). The results indicated that the concentration of 226Ra, 232Th, and 40K in grain samples was ranged from 56.97 to 86.13 Bq.kg−1, from 34.71 to 52.14 Bq.kg−1, and from 517.05 to 997.59 Bq.kg−1, respectively. The results of the average annual ingestion dose of natural radionuclides of 226Ra, 232Th, and 40K were found to be 66.555, 35.199, and 15.328 μSv y−1, respectively. These results are below the standard worldwide value (290 μSv y−1) that was reported by UNSCEAR. Therefore, the studied samples are considered safe in terms of the radiological health hazards, and there is no health hazard from the grain in this region.